Psychological stress, exercise and immunity - Perna, F. M.; Schneiderman, N.; LaPerriere, A. (International Journal of Sports Medicine, 1997)
In terms of cardiovascular, endocrine and immune responses, acute high-intensity aerobic exercise stress may be considered as a subcategory of stressful active coping. The cardiorespiratory responses of both include increases in heart rate, cardiac output, systolic blood pressure, skeletal muscle vasodilation and oxygen consumption. Neurohormonal responses include increases in catecholamines as well as elevations in cortisol under high but relatively low sympathetic activation. Immune system responses include increases in natural killer (NK) cell number and cytotoxicity and suppressor/cytotoxic lymphocytes as well as decreased proliferative response to mitogens. Task and recovery periods for both acute psychological stress or exercise show biphasic changes in immune response such that immune status is negatively impacted during recovery. Chronic life stressors influence acute cardiovascular, endocrine and immune responses to acute stressors. In addition, both chronic stress and unusually heavy chronic exercise can negatively impact immune status. Given impaired immune status following chronic stress and interactive effects of acute and chronic stressors (e.g. blunted acute NK responses to acute stressors), it is suggested that these factors may extend the window of vulnerability for infectious agents to act following acute psychological (e.g. examinations) or strenuous exercise (competitive athletics) stressors.